2020
DOI: 10.1002/jmv.26451
|View full text |Cite
|
Sign up to set email alerts
|

Considerations on oral manifestations of COVID‐19

Abstract: Since the first confirmed cases in the end of 2019 in the city of Wuhan, Hubei province in China, COVID‐19 has spread around the world, totaling, until July 25th, 2020, 15.785.641 confirmed cases and 640.016 deaths [1] . This article is protected by copyright. All rights reserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
12

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 16 publications
2
32
0
12
Order By: Relevance
“…According to Bezerra et al ( 50 ), it is reasonable to think that COVID-19 systemic immune deregulation may cause a more prolonged immune imbalance, which could predispose these late, secondary oral lesions. In addition, as stated by de Sousa et al ( 13 ), most patients developed oral mucosal injury during the hospitalization period, which supports the hypothesis of coinfections, immunity impairment, and adverse reactions to COVID-19 treatment medications.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…According to Bezerra et al ( 50 ), it is reasonable to think that COVID-19 systemic immune deregulation may cause a more prolonged immune imbalance, which could predispose these late, secondary oral lesions. In addition, as stated by de Sousa et al ( 13 ), most patients developed oral mucosal injury during the hospitalization period, which supports the hypothesis of coinfections, immunity impairment, and adverse reactions to COVID-19 treatment medications.…”
Section: Discussionsupporting
confidence: 74%
“…The most common skin lesions in these subjects include erythematous rash, urticaria, and vesicle formation, especially localized on the trunk, which seems to be the anatomic region most involved ( 5 , 8 ). Oral lesions, such as unspecific ulceration, desquamative gingivitis, petechiae, and coinfections, such as candidiasis ( 9 13 ), have also been reported. Moreover, Xu et al ( 14 ) reported a high level of expression of ACE2 receptors in epithelial cells of the oral mucosa, particularly tongue epithelial cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 5 , 6 According to the associated studies, the most frequent oral finding was oral ulceration, and there were distinct clinical patterns observed in different case studies. 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 Despite growing literatures investigating oral presentations in COVID-19 patients, few of them provide deep insight into oral ulcerative lesions, the most frequent but diverse one. The detailed clinical features, histological findings, immune profile, and the possible underlying pathogenetic mechanism of the oral ulcerative lesions are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…The etiology of oral lesions in patients with COVID‐19 is still uncertain and seems to be multi‐factorial. The appearance of such lesions may be related to the direct or indirect action of SARS‐CoV‐2 on the oral mucosa cells, hypersensitivity of drugs used in the treatment of COVID‐19,downgrading of the general state of health of the patient due to the disease and long period of hospitalization [ 15 ]. There may be a link between COVID-19 and oral manifestations, but these signs may often go undetected due to a lack of intraoral examination during hospital admission [ 16 ].…”
Section: Introductionmentioning
confidence: 99%